Abstract art and cortical motor activation: an EEG study - Umilta', Maria Alessandra; Berchio, Cristina; Sestito, Mariateresa; Freedberg, David; Gallese, Vittorio (Frontiers in Human Neuroscience, 2012)
The role of the motor system in the perception of visual art remains to be better understood. Earlier studies on the visual perception of abstract art (from Gestalt theory, as in Arnheim 1954 and 1988, to balance preference studies as in Locher and Stappers, 2002, and more recent work by Locher et al 2007, Redies, 2007, and Taylor et al, 2011), neglected the question, while the field of neuroesthetics (Zeki, 1999; Ramachandran and Hirstein, 1999) mostly concentrated on figurative works. Much recent work has demonstrated the multimodality of vision, encompassing the activation of motor, somatosensory and viscero-motor brain regions. The present study investigated whether the observation of high-resolution digitized static images of abstract paintings by Lucio Fontana is associated with specific cortical motor activation in the beholder’s brain. Mu rhythm suppression was evoked by the observation of original art works but not by control stimuli (as in the case of graphically modified versions of these works). Most interestingly, previous visual exposure to the stimuli did not affect the mu rhythm suppression induced by their observation. The present results clearly show the involvement of the cortical motor system in the viewing of static abstract art works.